Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12884-022-05336-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma vitamin D levels across pregnancy are not associated with neonatal birthweight: findings from an Australian cohort study of low-risk pregnant women

Abstract: Background In utero environments can be highly influential in contributing to the development of offspring obesity. Specifically, vitamin D deficiency during pregnancy is associated with adverse maternal and child health outcomes, however its relationship with offspring obesity remains unclear. We assessed maternal vitamin D status across pregnancy, change in plasma vitamin D concentrations and associations with neonatal birthweight, macrosomia and large for gestational age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Together with other VD supplementation avenues (22.4%), 77.6% of included women took in VD with vitamin complexes. An Australian cohort study of low-risk pregnant women reported much higher supplementation practices: almost all of the included women (97.7%) took some form of VD-containing supplement during pregnancy, with 93.5% prenatal multivitamin usage and 62.6% taking VD together or without pregnancy multivitamins [36]. Low awareness about VD content was also found among Irish women, as 57.9% of those women who reported not taking any VD supplements had actually taken prenatal vitamins including VD [37].…”
Section: Discussionmentioning
confidence: 99%
“…Together with other VD supplementation avenues (22.4%), 77.6% of included women took in VD with vitamin complexes. An Australian cohort study of low-risk pregnant women reported much higher supplementation practices: almost all of the included women (97.7%) took some form of VD-containing supplement during pregnancy, with 93.5% prenatal multivitamin usage and 62.6% taking VD together or without pregnancy multivitamins [36]. Low awareness about VD content was also found among Irish women, as 57.9% of those women who reported not taking any VD supplements had actually taken prenatal vitamins including VD [37].…”
Section: Discussionmentioning
confidence: 99%
“…The protective association between neonatal vitamin D and early-onset persistent eczema suggests that vitamin D supplementation during pregnancy might reduce the risk of this outcome. Neonatal vitamin D level is a reflection of maternal vitamin D status, and supplementation during pregnancy increases neonatal vitamin D [18,19]. Current guidelines [24][25][26] do not recommend the routine use of vitamin D supplementation during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…We observed consistent evidence that for every 10 nmol/L increase in neonatal vitamin D, the risk of eczema was reduced by approximately 11%. Maternal vitamin D level during pregnancy is a key driver of neonatal vitamin D [18], and vitamin D supplementation during pregnancy increases the neonatal vitamin D level [19]. Despite this, clinical trials of maternal vitamin D supplementation during pregnancy have not shown consistent protective effects [20][21][22][23], possibly due to lack of power, and/or contamination of the control group.…”
Section: Introductionmentioning
confidence: 99%